2005
DOI: 10.12968/ijpn.2005.11.12.20230
|View full text |Cite
|
Sign up to set email alerts
|

Nursing documentation: non-physical dimensions of end-of-life care in acute wards

Abstract: there is a strong need for: (1) education about both the impact of non-physical dimensions of patients' lives and the effective documentation of these dimensions; and (2) up-grading of documentation tools to better facilitate documentation of non-physical aspects of palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…One of the major issues was the lack of documentation concerning a series of nursing care topics. Many studies showed the predominance of documentation of a biomedical nature and insufficient recording of psychological, social, cultural and spiritual aspects of care (Hegarty et al. 2005, Altken et al.…”
Section: Resultsmentioning
confidence: 99%
“…One of the major issues was the lack of documentation concerning a series of nursing care topics. Many studies showed the predominance of documentation of a biomedical nature and insufficient recording of psychological, social, cultural and spiritual aspects of care (Hegarty et al. 2005, Altken et al.…”
Section: Resultsmentioning
confidence: 99%
“…27 Given the prevalence of chronic disease, it is unsurprising that there has been much debate in the literature about the shortcomings of acute care in meeting the needs of those whose disease is progressing or who are dying. 1,2,28,29 While patients living with chronic disease may require treatment intermittently for acute episodes of illness, professionals should also remember that an acute episode occurs against a backdrop of ongoing and often advancing disease and may, in fact, represent a terminal event. Caring for patients in these circumstances requires a heightened sensitivity to the medical and ethical implications of treatment, 30 and the courage to break from, when appropriate, treatment dominated routine.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though patients and family members expressed preferences when asked about end-of-life care, in almost 30% of the included data their views were not documented. [55] Family presence during counseling, [50] family-focused nursing diagnoses [56] and psychosocial, spiritual and cultural aspects of patient and family care [57] were found to be important to document, however infrequently this is actually done. It was found that family members are a supportive resource in care; however, this is not as well documented as it should be.…”
Section: Content Of Family Documentationmentioning
confidence: 99%
“…Hegarty et al [57] noted that the families' concerns were part of the nursing care, but these concerns only rarely showed up in the documentation. According to Heyland et al, [55] the preferences which patients and families expressed were not consistent with what was written in the documentation.…”
Section: Content Of Family Documentationmentioning
confidence: 99%
See 1 more Smart Citation